Efeitos de consequências programadas e do monitoramento sobre a manutenção do seguimento de regras discrepantes em pessoas com comportamentos depressivos autorrelatados - Zapparoli, Heloísa Ribeiro (2025)
Excessive rule-following is considered central to psychological suffering, but evidence for this relation remains scarce and inconclusive. Two studies investigated the effects of variables on the maintenance of discrepant rule-following in individuals with self-reported depressive symptoms. In Study 1, the effects of programmed consequences of gain or loss were evaluated. Sixty undergraduate students were classified in levels of symptom (high or low) based on questionnaire scores and distributed across gain and loss conditions, forming four groups. The task consisted of selecting one of two comparison stimuli in the presence of a contextual cue (i.e., a green or red circle). A rule instructed participants to choose the most similar stimulus in the presence of green and the most different in the presence of red. In the gain condition, one point was earned per correct response; in the loss condition, one point was lost per error. Four blocks of 20 trials were conducted. In the odd blocks the contingencies corresponded to the rule. In the even blocks they turned discrepant, without signaling. Greater abandonment of discrepant rules was observed in the loss condition, regardless of symptom levels. Study 2 assessed the effect of monitoring under loss contingencies. Thirty-two undergraduates, also classified by symptom levels, performed a similar task. Monitoring was introduced in one discrepant block. Half of the participants were monitored in the first discrepant block and the other half in the second. Greater maintenance of rule-following occurred when monitoring was present in the first discrepant block, persisting into the subsequent discrepant block without monitoring specially among participants with high symptom levels. Results suggest that rule-following tends to decrease when it produces loss of reinforcement, regardless of the level of symptoms, but this effect can be reversed when initial contact with contingency change occurs under monitoring. The complexity of what is considered depression is discussed along with the possibility that excessive rule-following may be relevant only in some cases, but not in a generic way.